Rheumatoid arthritis triple therapy compared with etanercept: difference in infectious and gastrointestinal adverse events. (10th December 2016) - Quach, Lien T.; Chang, Bei-Hung; Brophy, Mary T.; Soe Thwin, Soe; Hannagan, Keri; O'Dell, James R.
Abstract : Objective. The main aim of this study was to examine the differences between triple therapy (T: SSZ and HCQ added to MTX) and etanercept (E) added to MTX with regard to the infectious and gastrointestinal (GI) adverse events (AEs) reported in The Rheumatoid Arthritis Comparison of Active Therapies Trial. Methods. The patients were 353 RA MTX incomplete responders who were randomized to T (n = 178) or E (n = 175). Of these, 88 patients were switched to the alternative treatment from the initial treatment (E or T) at 24 weeks per protocol. Infectious and GI serious AEs (SAEs) and non-serious AEs (NAEs) were reported during 48 and 4 weeks after the intervention period. Generalized linear models were used to estimate the incidence rate ratios (IRRs) of AEs between the two therapies. Results. Patients on E therapy were more likely to have infectious NAEs (IRR = 1.56, 95% CI: 1.11, 2.19). There was a greater number of infectious SAEs that occurred when patients received E than T therapy [12 E (6.9%) vs 4 T (2.2%), P = 0.19]. Pneumonia was the most common infectious SAE for both treatments [6 E (3.4%) and 2 T (1.1%)]. Conversely, patients who were on E were less likely to have GI NAEs than those on T therapy (IRR = 0.62, 95% CI: 0.40, 0.94). The most common GI SAE reported was GI haemorrhage, which occurred among three patients on E (1.7%). Conclusion. This study provides evidence of different likelihoods of infectious and GI AEs associated with two common, equally effective treatments for RA patients who have had incomplete responses to MTX. Trial registration: ClinicalTrials.gov, http://clinicaltrials.gov, NCT00405275.